2017
DOI: 10.1038/s41598-017-17232-1
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting unexploited antibiotics in search of new antibacterial drug candidates: the case of γ-actinorhodin

Abstract: Of the thousands of natural product antibiotics discovered to date, only a handful have been developed for the treatment of bacterial infection. The clinically unexploited majority likely include compounds with untapped potential as antibacterial drugs, and in view of the ever-growing unmet medical need for such agents, warrant systematic re-evaluation. Here we revisit the actinorhodins, a class that was first reported 70 years ago, but which remains poorly characterized. We show that γ-actinorhodin possesses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 37 publications
(44 reference statements)
4
25
0
Order By: Relevance
“…As expected, most of the compounds identified in the chemical analysis were reported before as secondary metabolites of Streptomyces , such as naringenin, the aglycone of narirutin (Álvarez‐Álvarez et al ), γ ‐actinorhodin (Nass et al ), germicidins (Čihák et al ), geldanamycin (Fukuyo et al ), doxorubicin (Arcamone et al ), 4,5‐dihydrogeldanamycin (Lin et al ), albaflavenone (Lin and Cane ; Čihák et al ), lasalocid (Shichijo et al ), antimycin B2 (Han et al ), linearolide A (Ueki et al ) and ascomycin (Griffiths ). Interestingly, to our knowledge, genistein‐7‐ O ‐glucuronide, phenyl acetic acid, 7,3’,4’‐trihydroxyflavanone, resveratrol and mycophenolic acid have never been reported before in Streptomyces .…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…As expected, most of the compounds identified in the chemical analysis were reported before as secondary metabolites of Streptomyces , such as naringenin, the aglycone of narirutin (Álvarez‐Álvarez et al ), γ ‐actinorhodin (Nass et al ), germicidins (Čihák et al ), geldanamycin (Fukuyo et al ), doxorubicin (Arcamone et al ), 4,5‐dihydrogeldanamycin (Lin et al ), albaflavenone (Lin and Cane ; Čihák et al ), lasalocid (Shichijo et al ), antimycin B2 (Han et al ), linearolide A (Ueki et al ) and ascomycin (Griffiths ). Interestingly, to our knowledge, genistein‐7‐ O ‐glucuronide, phenyl acetic acid, 7,3’,4’‐trihydroxyflavanone, resveratrol and mycophenolic acid have never been reported before in Streptomyces .…”
Section: Discussionsupporting
confidence: 60%
“…In addition, several compounds identified in the extract have been associated in the literature with antibacterial activity. So, γ ‐actinorhodin (Nass et al ), geldanamycin (Shin et al ), doxorubicin (Arcamone et al ), mycophenolic acid (Merrigan et al ), germicidin A and germicidin analogous (Petersen et al ; Čihák et al ), albaflavenone (Lin and cane ; Čihák et al ) and antimycin B2 (Han et al ) are likely to be the compounds responsible for the antibacterial activity reported in this study. Interestingly, some of the identified compounds have been associated with activities that can be considered very important for human applications.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Streptomyces spp. is considered to be the major producers of about half of all naturally occurring antibiotics [3]. Streptomyces spp.…”
Section: Introductionmentioning
confidence: 99%
“…Another promising strategy for combating antibiotic resistance is to resurrect discarded antibiotics by reducing undesired side-effects and improving target affinity (Maviglia, Nestorini, & Pennisi, 2009;Nass et al, 2017). Synthesizing prodrug versions of an antibiotic is one confirmed method for masking activity or shifting toxicity (Blondiaux et al, 2017;Istvan et al, 2017;Pires et al, 2015).…”
Section: Introductionmentioning
confidence: 99%